Record Open‐Circuit Voltage Wide‐Bandgap Perovskite Solar Cells Utilizing 2D/3D Perovskite Heterostructure. Issue 21 (24th April 2019) - Gharibzadeh, Saba; Abdollahi Nejand, Bahram; Jakoby, Marius; Abzieher, Tobias; Hauschild, Dirk; Moghadamzadeh, Somayeh; Schwenzer, Jonas A.; Brenner, Philipp; Schmager, Raphael; Haghighirad, Amir Abbas; Weinhardt, Lothar; Lemmer, Uli; et al.
Abstract: In this work, the authors realize stable and highly efficient wide‐bandgap perovskite solar cells that promise high power conversion efficiencies (PCE) and are likely to play a key role in next generation multi‐junction photovoltaics (PV). This work reports on wide‐bandgap (≈1.72 eV) perovskite solar cells exhibiting stable PCEs of up to 19.4% and a remarkably high open‐circuit voltage ( V OC ) of 1.31 V. The V OC ‐to‐bandgap ratio is the highest reported for wide‐bandgap organic−inorganic hybrid perovskite solar cells and the V OC also exceeds 90% of the theoretical maximum, defined by the Shockley–Queisser limit. This advance is based on creating a hybrid 2D/3D perovskite heterostructure. By spin coating n ‐butylammonium bromide on the double‐cation perovskite absorber layer, a thin 2D Ruddlesden–Popper perovskite layer of intermediate phases is formed, which mitigates nonradiative recombination in the perovskite absorber layer. As a result, V OC is enhanced by 80 mV. Abstract : By coating n ‐butylammonium bromide on wide‐bandgap double‐cation perovskite absorber layers ( E G ≈ 1.72 eV), a thin 2D Ruddlesden–Popper perovskite layer of intermediate phase is formed. The resulting heterostructure mitigates nonradiative recombination and enables a high open‐circuit voltage of up to 1.31 V and stable power output efficiencies of up to 19.4%.